Kemukjizatan retorika pengulangan ayat ” فَبِأَيِّ آلَاءِ رَبِّكُمَا تُكَذِّبَانِ” dalam surah Ar-Rahman: Analisis Ilmu Ma’ani - Maryam, Ayu Siti (Maliki Interdisciplinary Journal, 2026)
This study examines the rhetorical wonder of the verse “Fabi Ayyi Ālā’i Rabbikumā Tukażżibān” in Surah al-Raḥmān through the perspective of Ma‘ānī. This verse is repeated 31 times in various contexts related to the blessings of Allah, the signs of His power, the Day of Judgment, and the rewards for humans and jinn. This repetition often draws attention because it uses the same wording yet still conveys diverse meanings depending on the context of the accompanying verses. This study aims to analyze the rhetorical function of this verse and explain its miraculous aspects within the framework of Ma‘ānī studies. The method employed is library research using a qualitative approach. Data were obtained from the Qur’an, exegetical works, balāghah literature, and relevant prior research, and were then analyzed using a descriptive-analytical approach. The results indicate that these verses serve several rhetorical functions: at-taukīd (emphasis), at-tanbīh (warning), and at-taubīkh (reprimand). These functions indicate that the repetition in Surah al-Raḥmān is not merely a repetition of words, but a means to reinforce the message, instill meaning, and cultivate the spiritual awareness of its readers. Thus, this verse serves as one of the forms of the Qur’an’s rhetorical miracles, demonstrating the harmony between language, context, and the intended meaning.